PRIVACY RIGHTS IN THE AGE OF CYBERCRIME: A CRIMINAL LAW PERSPECTIVE - Gupta, Ashwani Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The rapid advancement of technology in the digital age has transformed how individuals interact, communicate, and conduct business online, but it has also given rise to significant challenges regarding the protection of privacy rights. Data breaches, hacking, identity theft, and cyberstalking are just a few examples of the many forms of cybercrime that affect people’s right to privacy and the protection of their private information. Looking at cybercrime from a criminal law standpoint, this abstract explores the increasing conflict between private rights and the prevalence of the crime. Cybercriminals take advantage of the internet’s anonymity and worldwide reach, making it difficult to enforce privacy regulations in the digital world. Cybercrime presents unique issues that current legal frameworks are ill-equipped to handle; this paper argues that this calls for new laws, more robust cybersecurity measures, and more international cooperation. The significance of developing criminal laws to defend people’ rights against cybercrime is highlighted by the core issue of striking a balance between protecting privacy and guaranteeing security in an ever more interconnected world.